ANALISIS SENSITIVITAS RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM AWAL DAN AKHIR TAHUN PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Indah Yuliana (El-QUDWAH, 2008)
An effect is so affected and inseperable from the condition of its issuing company performance (emitten). A valuation effect can be done by fundamental and technical approach. From the followers of the fundamental analysis, shares price is a reflection from related company value. The fluctuation of shares price traded in stock market determined by market force. If market asses that the issuing company of shares is in good condition, so the shares price of the company increases. On the other hand, if the company is undervalued by the market, the shares price of company decrease even it is lower than the price which is in principal market. Hence, a bargaining is in secondary market among investors determining the shares price of company. The purpose of this research is First, to analyze the sensitivity of liquidity and profitability simultaneously to the beginning and the end of the year of shares price. Second, to analyze the liquidity and profitability affecting dominantly to the beginning and the end of the year of shares price in Transportation Company listed on Indonesian Stock Market. In this research, researcher takes two hypotheses that is first, the sensitivity liquidity ratio to the beginning and the end of the year of shares price. Second, the profitability ratio affects to the beginning and the end of the year of shares price in Transportation Company listed on Indonesian Stock Market. The analysis tool used in this research, first, classical assumption test to examine the first hypothesis, Multicolinierity test, Heteroscedastisity test, Normality test. Second, it is a double regression linier analysis. From the result of this research, it can be taken that (1) the sensitivity of liquidity and profitability ratio to the beginning and the end of the year of shares price. The sensitivity great raised by liquidity and profitability variable to the beginning year of shares price in transportation service is 17.1% and the remain is 82.9% affected by another variable excluded in an equation model. Meanwhile the sensitivity great raised by liquidity and profitability variable to the end year of company shares price in transportation service is 27.3% and the remain is 72.7% affected by another variable excluded in an equation model.  (2) The liquidity ratio affects more dominantly to the beginning and the end of the year of shares price proven by the statistical value, value TTest (2.311) is bigger than TTable (2.0595). Therefore, it can be concluded that the liquidity of transportation company listed on Indonesian Stock market influecing to the beginning and the end of the year of shares price. It is compared by the profitability does not influence dominantly to the beginning and the end of the year of shares price proven by the statistical value, value TTest (-0.1,145) is lower than TTable (-2.0559), it means that if the transportation company service has a higher profitability, so it doesn’t influence the beginning and the end of the year of shares price yet.Key words: Liquidity Ratio, Profitability, The Beginning and the End of the Year of Shares price